Effects of Tai Chi Exercise on Reducing Falls and Improving Balance Performance in Parkinson’s Disease: A Meta-Analysis - Hsin-Hsuan Liu; Nai-Chen Yeh; Yi-Fan Wu; Yea-Ru Yang; Ray-Yau Wang; Fang-Yu Cheng (Parkinson's Disease)
Introduction. Parkinson’s disease (PD) is a common neurodegenerative disorder that may increase the risk of falls, functional limitation, and balance deficits. Tai Chi was used as an option for improving balance in people with PD. The aim of this meta-analysis was to evaluate the effects of Tai Chi on falls, balance, and functional mobility in individuals with PD. Method. The literature search was conducted in PubMed, the Cochrane Library, CINAHL, PEDro, Medline, Embase, sportDISCUS, Trip, and the National Digital Library of Theses and Dissertations in Taiwan. Randomized controlled trials (RCTs) analyzing the effects of Tai Chi, compared to no intervention or to other physical training, on falls, functional mobility, and balance in PD patients were selected. The outcome measurements included fall rates, Berg Balance Scale (BBS), Functional Reach (FR) test, and the Timed Up and Go (TUG) test. Two reviewers independently assessed the methodological quality and extracted data from the studies using the PEDro scale. Results. Five RCTs that included a total of 355 PD patients were included in this review. The quality of evidence in these studies was rated as moderate to high. Compared to no intervention or other physical training, Tai Chi significantly decreased fall rates (odds ratio = 0.47, 95% confidence interval (CI) 0.30 to 0.74, and p=0.001) and significantly improved balance and functional mobility (BBS mean difference (MD) = 3.47, 95% CI 2.11 to 4.80, and p<0.001; FR MD = 3.55 cm, 95% CI 1.88 to 5.23, and p<0.001; TUG MD = −1.06 s, 95% CI −1.61 to −0.51, and p<0.001) in people with PD. Conclusion. This meta-analysis provides moderate- to high-quality evidence from five RCTs that Tai Chi could be a good physical training strategy for preventing falls and improving balance and functional mobility in people with PD.